Antiretroviral Effects on Host Lipoproteins Are Associated With Changes in Hepatitis C Virus (HCV) RNA Levels in Human Immunodeficiency Virus/HCV Coinfected Individuals. (12th May 2015) - Naggie, Susanna; Patel, Keyur; Yang, Lan-Yan; Chow, Shein-Chung; Johnson, Victoria; Guyton, John R.; Muir, Andrew J.; Sulkowski, Mark; Hicks, Charles
Abstract: We evaluated the impact of antiretroviral-induced dyslipidemia on hepatitis C virus (HCV) biogenesis in human immunodeficiency virus (HIV)/HCV coinfected patients. This study used serum samples from antiretroviral-naive HIV/HCV patients initiating their first regimen as part of AIDS Clinical Trials Group study protocols (A5142, A5202). Initiation of antiretrovirals increased most lipoproteins and apolipoproteins. In the multivariable model, changes in apolipoproteins were associated with changes in log10 HCV RNA from baseline to week-24 of therapy. Off-target lipogenic changes need to be considered in the context of liver and other metabolic disease in HIV/HCV patients.